UPAYA APARAT LEMBAGA PEMASYARAKATAN DALAM MENCEGAH PENYELUNDUPAN NARKOTIKA DI LEMBAGA PEMASYARAKATAN (STUDI DI LEMBAGA PEMASYARAKATAN KELAS II B LUWUK) - ARIANTI A OGOTAN (Jurnal Yustisiabel, 2019)
Narcotics are substances or drugs derived from plant crops or not, whether synthetic or semisintetis, which can cause a decrease or alteration of consciousness, loss of taste, reduce to eliminate pain, and may cause dependency. Illicit traffic in narcotic drugs and abuse becomes a shared responsibility of all Nations in the world. This research aims to know the efforts of correctional authorities in preventing the smuggling of narcotics at the correctional facility class II B Luwuk and to know the drag correctional authorities in preventing smuggling Narcotics in the correctional facility class II B of Luwuk. This Research method using this type of Empirical Juridical Research i.e. research won the data directly from the field and using the method of qualitative analysis of deskrpstif. Research results Showed the efforts of correctional apparatus Apparatus in preventing smuggling of narcotics in class II correctional facility.